Eksplorasi Kompleksitas Batuan Piroklastik: Studi Tentang Sifat, Proses Pembentukan, Komposisi Mineral, dan Strukturnya - Asna Arif Fathonah; Moch Ridho Saputra; Nisa Hanna Fazira; Wahyu Kurniawati (International Forum of Researchers and Lecturers, 2024)
Rocks are naturally formed solid objects which are a collection of minerals, both similar and dissimilar, in certain proportions. Minerals are the building blocks of each type of rock. In the beginning, rocks came from magma. The types of rock that exist include pyroclastic rocks. Pyroclastic rocks contain contents that are of economic value and useful for human life. The type of method used is a qualitative research method. The data collection technique in this method is the literature study method. The method in this research focuses on in-depth observations from various reading sources such as books and scientific journals. Pyroclastic rocks are rocks formed by the lithification process of loose materials thrown from volcanic centers in explosive eruptions, which are then transported through the media of gas, wind and then deposited on dry land or in bodies of water. In fact, pyroclastics are almost the same as sedimentary rocks, but the difference is that sedimentary rocks come from the weathering of previous rocks. Meanwhile, pyroclastic rocks come from volcanic eruptions, meaning there is no weathering process.